Hydrogen-enhanced oxidation of ferrite phase in stainless steel cladding and the contribution to stress corrosion cracking in deaerated high temperature water - Cui, T; Dong, H; Xu, X; Ma, J; Lu, Z; Tang, Y; Pan, D; Lozano-Perez, S; Shoji, T (Elsevier, 2021)
Oxide film properties and stress corrosion cracking (SCC) behaviour are investigated in the 308L stainless steel cladding layer with and without being H-charged in a deaerated high temperature water. Phase boundary (PB) has lower oxidation resistance than austenite and δ-ferrite matrix. A compact and high Cr content-bearing inner oxide layer improves the oxidation resistance of the δ-ferrite phase without H charging. H-induced PB penetration oxidation and grain boundary (GB) preferential oxidation are observed in H-charged specimen due to the PB and GB act as H trapping sites. Charged H decreases the oxidation resistance of δ-ferrite and austenite. δ-Ferrite acts as a path for H diffusing and H flux facilitates mass transport, resulting in the poor oxidation resistance of δ-ferrite. The mechanism underlying the effect of H on the oxidation behaviours of δ-ferrite and austenitic phases, as well as SCC performance, are discussed.